DESIGN CRITERIA OF MODERN SHOPPING CENTRE BUILDING BASED ON PUBLIC PEDESTRIAN SPACE - Kapindro Hari Sasmita; Bambang Soemardiono; Vincentius Totok Noerwasito (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2020)
Mobility contributes to quality of life (Muller, 2016). In Indonesia, shopping centre buildings and urban pedestrian spaces have not been supporting each other in accommodating public pedestrian mobility. It lets people to drive more automobiles instead of walking even though their settlements are actually convenient from the commercial places. This problem is further causing the other matters such as traffic jam, accidence, air pollution, anxiety, and so on. By considering this problem, it is important to transform the design criteria of the modern shopping centre building to be not only serving as commercial destinations, but also space for public pedestrians that provides good mobility in urban environment, so that the walking lifestyle could be popular again in Indonesia. This research is aimed to identify design criteria of modern shopping centre buildings that are based on public pedestrian space. The criteria is expected to be new standard in planning and designing future shopping centre buildings in Indonesian cities. The Evaluative Method is utilized in this research involving a theory of Urban Mobility as the main parameter.